THE EFFECT OF ABO BLOOD GROUP ON COVID-19 IN PREGNANCY - Sri Sulistyowati; Nutria Widya Purna Anggraini; Soetrisno Soetrisno; Eric Edwin Yuliantara; Supriyadi Hari Respati; Muhammad Adrianes Bachnas; Wisnu Prabowo; Hafi Nurinasari; Dympna Pramelita; Dewi Setiyawati; Metharisa Sujana; Aldi Firmansyah (Faculty of Medicine, Universitas Islam Indonesia, 2021)
Background: The COVID-19 virus has spread throughout the world and has been declared as a global pandemic by WHO. Some population groups are more susceptible to COVID-19, and one of them is pregnant women. Pregnancy increases risks of the COVID-19, especially thrombotic complications. The SARS-CoV-2 infection may vary widely from asymptomatic to severe infection. Some studies have shown that ABO blood group can be a marker of susceptibility to some disease progression. Objective:This study aims to investigate relationships between the ABO blood group, the COVID-19 infection and its complications in pregnant women at Dr. Moewardi Hospital, Surakarta.Methods: This study was an observational analytic study with a cross-sectional study design involving 40 pregnant women infected with COVID-19 at Dr. Moewardi Hospital, Surakarta. COVID-19 PCR swabs on the women were administered on their oropharynx and nasopharynx, and laboratory examination of the ABO blood group in all samples was performed. Comparative data distribution of blood groups in the population and the global population distribution were calculated by Chi Square Goodness of Fit. Comparative data between ABO blood group distributions, blood parameters and complications (respiratory, thrombotic, other infections, and death) were calculated by Chi square test and then by One-Way ANOVA. Next, correlation tests for the complications of the blood group and the ages applied a multinomial regression.Results: There were significant differences of thrombotic complications on the blood group of pregnant women infected with COVID-19 (p=0.027). Blood type B significantly tended to experience thrombotic complications when compared to other blood groups (p=0.022).Conclusion: The ABO blood group could affect the complication levels in the pregnant women infected with the COVID 19.